Impulsivity, peer pressure, and social media usage as predictors of addictive gambling behavior among undergraduates - Ajayi, Mojisola S.; Lawal, Yusuf O.; Uye, Emmanuel E. (Journal of Indonesian Psychological Science (JIPS), 2024)
The increased rate of gambling in our society has become a menace that affects nearly every Nigerian youth, including undergraduates. Studies using different predictors of addictive gambling behavior have produced varying results. Therefore, this study investigated impulsivity, peer pressure, and social media usage as predictors of addictive gambling behavior among undergraduates in Nigeria. A cross-sectional survey design using the purposive sampling technique was used to select three universities. Data were collected from 258 undergraduates using validated scales. The collected data were analyzed using zero-order correlation and multiple regression analysis. The result revealed that peer pressure was significantly correlated with addictive gambling behavior. Also, impulsivity, peer pressure, and social media usage jointly predicted addictive gambling behavior. However, only peer pressure independently predicted addictive gambling behavior. The conclusion is that peer pressure is a strong predictor of addictive gambling behavior. The implication of this finding is that parents, university authorities, and other stakeholders should design programmes and policies to reduce peer pressure on problem gambling. KEY WORDS: addictive gambling behavior; impulsivity; peer pressure; social media usage ABSTRAK Meningkatnya tingkat perjudian di masyarakat kita telah menjadi ancaman yang mempengaruhi hampir setiap pemuda Nigeria termasuk mahasiswa. Penelitian yang menggunakan prediktor yang berbeda dari perilaku perjudian yang membuat ketagihan telah memberikan hasil yang bervariasi. Oleh karena itu, penelitian ini menyelidiki impulsif, tekanan teman sebaya, dan penggunaan media sosial sebagai prediktor perilaku perjudian yang membuat ketagihan di kalangan mahasiswa di Nigeria. Desain survei cross-sectional menggunakan teknik purposive sampling digunakan untuk memilih tiga universitas. Data dikumpulkan dari 258 mahasiswa dengan menggunakan skala yang telah divalidasi. Data yang dikumpulkan dianalisis dengan menggunakan korelasi orde nol dan analisis regresi berganda. Hasilnya menunjukkan bahwa tekanan teman sebaya berkorelasi secara signifikan dengan perilaku perjudian yang membuat ketagihan. Selain itu, impulsif, tekanan teman sebaya, dan penggunaan media sosial secara bersama-sama memprediksi perilaku perjudian yang membuat ketagihan. Namun, hanya tekanan teman sebaya yang secara independen memprediksi perilaku perjudian yang membuat ketagihan. Kesimpulannya adalah bahwa tekanan teman sebaya adalah prediktor kuat dari perilaku perjudian yang membuat ketagihan. Implikasi dari temuan ini adalah bahwa orang tua, otoritas universitas, dan pemangku kepentingan lainnya harus merancang program dan kebijakan untuk mengurangi tekanan teman sebaya pada masalah perjudian KATA KUNCI perilaku perjudian adiktif; impulsif; tekanan teman sebaya; penggunaan media sosial Copyright ©2024. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0